Configurational and chain-mediational path-ways linking natural environment perception to restorative environmental perception - Genmao Wang; Shuangquan Zhang (PLoS ONE, 2026)
While the link between natural environment perception (NEP) and restorative environmental perception (REP) is well-established, the specific psychological mechanisms—how environmental preference (EP) and place attachment (PA) configure this relationship—remain underexplored. This study aims to bridge this gap by examining the symmetric and asymmetric pathways translating nature perception into restorative outcomes. Analyzing survey data from 432 visitors to Zhangjiajie National Forest Park, China, we employed Partial Least Squares Structural Equation Modeling (PLS-SEM) to test serial mediation and Fuzzy-set Qualitative Comparative Analysis (fsQCA) to identify equifinal configurations. PLS-SEM results indicate that NEP enhances REP directly and indirectly through EP. Furthermore, a significant serial mediation path (NEP → EP → PA → REP) was established. Complementing these findings, fsQCA revealed EP as a “core condition” across all configurations for high REP, whereas PA serves as a “peripheral condition.” Theoretically, these results identify environmental preference as the critical gatekeeper for restoration. Practically, they suggest managers should prioritize aesthetics that trigger immediate preference to enhance restorative experiences.